Thraulodes bonito sp. nov. (Ephemeroptera: Leptophlebiidae) from Rio de Janeiro State, Southeastern Brazil - Gonçalves, Inês Corrêa; Da-Silva, Elidiomar Ribeiro; Nessimian, Jorge Luiz (Zootaxa, 2013)
A new species of Thraulodes Ulmer, 1920 is described from Rio de Janeiro. The species resembles the recently published Thraulodes pelicanus Mariano and Froehlich, 2011 (in Mariano et al. 2011) due to the length and width of the penes. How-ever, Thraulodes bonito sp. nov. differs from this and all other species of the genus by the wide penes, the triangular shape of the styliger plate with median projection short and apex rounded, the abdominal color pattern and the presence of 1–3 weakly marked cross veins basal to bullae. The new species is described based on male imagos, female subimagos and nymphs.